Compound odontoma associated with mandibular impacted permanent central incisor - Seref Ezirganli; Ufuk Taşdemir; Ugur Gurer (Cumhuriyet University, 2012)
Odontomas are the most common benign odontogenic tumors that are hamartomas composed of various dental tissues, and there are two types, complex and compound. Compound odontomas are more prevalent than complex odontomas and consist of many teeth-like structures. Most of such lesions are asymptomatic. These lesions are generally diagnosed by routine radiological examination. The compound type is generally found in the anterior region of the maxilla. The etiology of these lesions has not been precisely explained. If there is absence of any contraindication, the treatment for odontomas is surgical excision.This article describes a case of compound odontoma associated with impacted central mandibular right permanent incisor in a 12-year-old female due to trauma. The odontoma was surgically removed with an impacted central incisor.